Phenotypic modulation of the mesangium reflected by contractile proteins in diabetes - Makino, H.; Kashihara, N.; Sugiyama, H.; Kanao, K.; Sekikawa, T.; Okamoto, K.; Maeshima, Y.; Ota, Z.; Nagai, R. (Diabetes (New York, N.Y.), 1996)
Phenotypic modulation of the mesangium reflected by contractile proteins in diabetes. H Makino , N Kashihara , H Sugiyama , K Kanao , T Sekikawa , K Okamoto , Y Maeshima , Z Ota and R Nagai Third Department of Internal Medicine, Okayama University Medical School, Japan. Abstract The phenotypic change of the mesangial cell is considered to play a pivotal role in the accumulation of extracellular matrix in diabetic nephropathy. This investigation was undertaken to evaluate the expression of the various isoforms of contractile proteins in the streptozocin (STZ)-induced diabetic rat kidney and in renal biopsy specimens from patients with diabetic nephropathy. Specific antibodies to myosin heavy chain isoforms (SM1, SM2, SMemb), caldesmon, and alpha-smooth muscle actin and cDNAs for SMemb were used. Increased expression of SMemb at the mRNA and protein levels was demonstrated at 1 week after STZ administration in the rat. Both levels were increased at 4 weeks. Mesangial staining of caldesmon was observed at 4 weeks and that of alpha-smooth muscle actin at 24 weeks. Immunohistochemical mesangial staining of the contractile proteins was pronounced in patients with diabetic nephropathy in contrast to the trace mesangial staining in normal control subjects. These results indicate that the phenotypic change in mesangial cells occurs in the early stages of diabetes and that several stages in phenotypic changes may exist. Expression of the contractile protein isoforms, especially SMemb, should serve as a new marker for the subsequent glomerular hypertrophy and sclerosis.